PERIODONTAL STATUS IN ADULTS EXPOSED TO SMOKED TOBACCO (CONVENTIONAL CIGARETTE VS. E-CIGARETTE): A SINGLE-CENTRE STUDY - Sadaf Arshi, Msc; Sana Masood, Bds; Sohail Saadat, Mds; Hira Fatima Waseem, Phd; Javaid Unar, Msc; Muhammad Uzair, Morthrcsed, Mfdrscsi, Mfdrsed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The increased trend of e-cigarettes among young adults has become a popular alternative to traditional cigarette smoking. Proponents believed it to be a safer alternative to smoking, citing lower exposure to many of the poisonous compounds found in tobacco smoke. However, the influence of e-cigarettes on oral health has gained increased interest among researchers and dental practitioners. Objectives: To assess the frequency of cigarette and e-cigarette smokers and to evaluate their association with periodontitis. Methods: An analytical cross-sectional study was conducted among 360 participants aged between 18 and 60 who visited the dental OPD of a public sector university. A validated questionnaire was administered to record demographic details, oral hygiene practices, and consumption practices of cigarettes and e-cigarettes. The periodontal assessment was done using CPI and CAL indices. The association of periodontal status among the groups was reported using Pearson’s chi-square test, while logistic regression was performed for multivariate analysis. Results: Participants with periodontitis reported more consumption of cigarettes, while participants with generalized chronic periodontitis reported more consumption of e-cigarettes. There was a significant association between the status of periodontitis and the type of smoker (p<0.001). The multivariate logistic regression analysis showed that e-cigarette smokers (OR=5.42), primary education (OR=4.29), graduates (OR=4.30), good oral hygiene (OR=0.04), fair oral hygiene (OR=0.05), and use of fluoridated tooth paste (OR=0.45) were significant risk factors for generalized periodontitis. Conclusion: Compared to conventional cigarette smokers, e-cigarette smokers have a profound detrimental effect on periodontium, measured by periodontal parameters (CAL & PD).